Manual of procedures for wildlife disease risk analysis (OIE and IUCN ParisFR, 2014)
Presents key concepts for wildlife disease risk analysis. Includes a detailed description of each step in the DRA process with examples taken from published and unpublished sources; and guidelines for successful interdisciplinary collaboration, technical, social and political considerations and some of the associated challenges.
Keywords: ANIMAL DISEASES